Presbyteroi w czasach Ojców Apostolskich - Szewczyk, Przemysław (Vox Patrum, 2011)
The ecclesiastical hierarchy, being a reality founded by Christ, is also subjected to historical evolution. The article discusses the history of pastoral service in the Church by analyzing the meaning of the word presbyteros in the writingsof the Apostolic Fathers. It is obvious that the term which is derived from the Greek language indicates a person who exercises a pastoral ministry in the church community emphasizing his seniority, but not necessarily old age. Only for Papias „presbuteros” is a real old man who, because of his age, is a living witness to the time of the Apostles. The authority of the witness made him a guardian of the faith, that is to say „episcopos”, the bishop. The writings of Ignatius of Antioch and Clement of Rome suggest that in their community „the elders” should not be really old, they form a group which has a different role from that of the bishop. It seems that with the end time of the bishops/old-men in the Church two realities were formed: the episcopacy and the colleges of the presbyter. The establishment of relations and the division of powers between the „presbuteroi” and the man appointed bishop of his church community was therefore one of the most important questions of Christianity in the time of the Apostolic Fathers.